Case Report: Refusal of an Veno-Arterial Extracorporeal Membrane Oxygenation Due to Malignant Disease? — An Extremely Rare Form of Cardiac Involvement in Acute Myeloid Leukemia - Zotzmann, Viviane; Wengenmayer, Tobias; Lang, Corinna N.; Staudacher, Dawid L.; Mueller-Peltzer, Katharina; Bamberg, Fabian; Marks, Reinhard; Bode, Christoph; Wäsch, Ralph (Frontiers in Medicine, 2021)
We report here on a 61-year-old patient with acute right heart failure of unclear etiology. Echocardiography revealed a myocardial mass infiltrating the heart, though, we assumed a cardiac lymphoma. A VA-ECMO was implanted as bridging for diagnosis and therapy. Our patient received chemotherapy, under which the tumor (of unknown etiology at this point) reached a partial remission. Nine months after first admission the patient developed acute myeloid leukemia with DNMT3a and TET2 mutations. Retrospective analysis of the cardiac biopsy revealed the identical mutations and matched with the diagnosis of an extremely rare primary extramedullary manifestation of an AML (myelosarcoma). The patient received induction-chemotherapy and was planned for consolidating allogeneic stem cell transplantation. From this case we conclude that an extracorporeal therapy should be discussed in younger patients even in case of an initially fatal appearing prognosis. In selected cases extracorporeal support can generate enough time for diagnosis and therapy. However, transparent planning, including discussion of best supportive care strategies involving the patient’s family are indispensable requirements for starting ECMO in such patients.